High HIV prevalence and associated factors in a remote community in the Rwenzori region of Western Uganda - John Rubaihayo; Akib Surat; Mughusu Ezekiel; Abaasa Andrew (MDPI AG, 2010)
In Uganda, previous studies have shown a tremendous decline in HIV prevalence over the past two decades due to changes in sexual behavior with a greater awareness of the risks involved. However, studies in Fort-Portal municipality, a rural town in Western Uganda, continued to show a persistent high HIV prevalence despite the various interventions in place. We conducted a study to establish the current magnitude of HIV prevalence and the factors associated with HIV prevalence in this community. This cross-sectional study was conducted between July and November 2008. Participants were residents of Fort-Portal municipality aged 15-49 years. A population-based HIV sero-survey and a clinical review of prevention of mother to child HIV transmission (PMTCT) and voluntary counseling and HIV Testing (VCT) records were used to collect quantitative data. An inteviewer administered structured questionnaire was used to collect qualitative data on social deographics, risk behaviour and community perceptions. Focus group discussions (FGDs) and in-depth interviews provided supplementary data on community perceptions. Logistic regression was used in the analysis. The overall HIV prevalence in the general population was 16.1% [95% CI; 12.5-20.6]. Prevalence was lower among women (14.5%; 95% CI; 10.0-19.7) but not significantly different from that among men (18.7%; 95% CI; 12.5-26.3) (c2=0.76, P=0.38). Having more than 2 sexual partners increased the odds of HIV by almost 2.5 times. None or low education and age over 35 years were independently associated with HIV prevalence (P<0.05). Most participants attributed the high HIV prevalence to promiscuity/multiple sexual partners (32.5%), followed by prostitution (13.6%), alcoholism (10.1%), carelessness (10.1%), poverty (9.7%), ignorance (9.5%)), rape (4.7%), drug abuse (3.6%) and others (malice/malevolence, laziness, etc.) (6.2%). Although there was a slight decline compared to previous reports, the results from this study confirm that HIV prevalence is still high in this community. In order to prevent new infections, the factors mentioned above need to be addressed, and we recommend that education aimed at changing individual behavior should be intensified in this community.